Impact of community share ownership schemes on development in Mberengwa district in Zimbabwe - Buka, Sympathy (Midlands State University, 2017)
The formative study focused on the impact of Share Ownership Schemes on development in Mberengwa District in Zimbabwe. The qualitative research established that some of the objectives of the programme were indeed relevant to the current challenges being faced by the people in rural Zimbabwe. The study also explored the impact of the share ownership schemes on individual and household levels with emphasis on the eradication of poverty. It explored the implementation process of the broad empowerment initiative in Mberengwa district and suggested that other dimensions of empowerment such as the political and social empowerment be included in order for real empowerment to be achieved. The implementation process was being hampered by inadequate funding, bureaucratic bungling, political interference and general lack of a clear direction on the way the programme was to be implemented. There were however a few success stories noted by the study.